Penerapan Metode Welch-Powell Improvement Pada Pewarnaan Graf Untuk Penjadwalan KBM SMAN 7 Mataram Menggunakan Python - Abi Rizky, Muhammad; Amrullah, Amrullah; Primajati, Gilang (Griya Journal of Mathematics Education and Application, 2025)
The preparation of teaching and learning schedules is often problematic, one of the reasons being the limited number of teachers, which means that one teacher has to teach several classes at the same time. This research is an applied study that aims to obtain a teaching and learning schedule without overlap by applying graph coloring using the Welch-Powell Improvement method. Graph coloring using the Welch-Powell Improvement method is a solution to solve scheduling problems at SMAN 7 Mataram. Based on the scheduling data, an adjacency matrix with a size of 898×898 and a chromatic number of 27 was obtained. The adjacency matrix was determined with the help of the Python programming language. The schedule was compiled by first creating a scheduling conflict graph based on the lesson schedule data, then coloring the graph using the Welch-Powell Improvement algorithm. Based on the coloring results obtained, the schedule was compiled by considering each node color. Subjects with the same color were scheduled at the same time and vice versa. The resulting class schedule was free of overlaps. This was because the chromatic number obtained in the graph coloring was smaller than the available time slots at SMAN 7 Mataram.